2020
DOI: 10.24843/jmhu.2020.v09.i04.p08
|View full text |Cite
|
Sign up to set email alerts
|

Valuasi Merek sebagai Jaminan Kredit Perbankan: Relevansi dalam Pembentukan Lembaga Penilai Kekayaan Intelektual

Abstract: This paper aims to examine the relevance of regulating the Intellectual Property Guarantee Institution as credit to banks in Indonesia in the future. The research method in this paper uses normative legal research, with a statutory approach and developing doctrines, as well as a comparative approach. The result found from this paper is that there is a need for synergy in the guarantee legal system in Indonesia, particularly in regulating intellectual property valuation, including the urgency to form an institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…This implies that the performing rights must be exercised by the LMKN so that, personally, the creator of the work does not have the authority to force royalty payments directly from the user of a work for commercial purposes. 14 From the three conceptions regarding performing rights in the HC Law above, it can be concluded that it must be managed, regulated, and implemented by LMKNs to channel royalties to the creators of works. In the context of copyrights to songs or music, musicians who sing songs created by one particular party to perform and be commercial, the performance rights in the form of royalties that must be received by the composers of the songs or music must be managed and distributed by the LMKN.…”
Section: The Legal Implications Of Performing Rights For Café Singers...mentioning
confidence: 99%
“…This implies that the performing rights must be exercised by the LMKN so that, personally, the creator of the work does not have the authority to force royalty payments directly from the user of a work for commercial purposes. 14 From the three conceptions regarding performing rights in the HC Law above, it can be concluded that it must be managed, regulated, and implemented by LMKNs to channel royalties to the creators of works. In the context of copyrights to songs or music, musicians who sing songs created by one particular party to perform and be commercial, the performance rights in the form of royalties that must be received by the composers of the songs or music must be managed and distributed by the LMKN.…”
Section: The Legal Implications Of Performing Rights For Café Singers...mentioning
confidence: 99%
“…Penggunaan merek oleh pemilik merek ataupun pihak lain lazim digunakan para pelaku usaha untuk tanda pembeda masing-masing produk barang maupun jasanya. Karena merek merupakan benda tidak berwujud (intangible asset) yang mempunyai nilai (value) bagi pemilik aset atau pemilik lain (Kurniawan, 2020).…”
Section: Latar Belakangunclassified
“…Merek sebagai aset bergerak tak berwujud maka pembebanan melalui jaminan fidusia dapat dilakukan dengan menggunakan beberapa komparisi pendekatan dalam penilaiannya, sebagai contoh pendekatan ini digunakan oleh Balai Harta Peninggalan Surabaya terhadap kasus pailit merek dagang "Animale" pada perusahaan PT. Mitra Garment Indoraya yang berdasar pada prosedur penilaian dengan pengaplikasian pendekatan yang berlaku sesuai dengan Standart Penilaian Indonesia dan Kode Etik Penilaian Indonesia, yaitu dengan pendekatan kuantatif (Kurniawan, 2020).…”
Section: Menurut Gunawan Widjaya Yang Dikutip Oleh Agung Sujatmiko Pe...unclassified
“…8 The value of social justice is a constitutional identity as well as stated in the Preamble to the 1945 Constitution of the Republic of Indonesia (hereinafter referred to as RI Constitution), and in particular, is a separate principle in the basis of the Indonesian state, namely Pancasila. 9 The essence of the value of social justice is what the state wants to realize through the Job Creation Law and its derivative regulations, namely PP UMK. One of the studies on the role of the state in protecting MSMEs was carried out by Dian regarding the role of banks in legal protection for SMEs affected by Covid-19, which discussed banking policies on MSMEs, especially those directly affected by the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%